REGIONAL GOVERNMENT PROBLEMATICS - Irianto, Bambang Sugeng; Assyifa, Salsabilah; Birawa, Satria (EQUALEGUM International Law Journal, 2023)
Background. In this reformation era, one of the areas of concern is the policy regarding Regional Autonomy, with the promulgation of the Law on Regional Government, which has brought significant changes to the relationship between the Center and the Regions. The purpose was to explain the effectiveness of the implementation of the Law on Regional Government. Research Method. This research used a normative legal approach. Analysis of an issue of the research using legal context and books of legal or law constitution. Findings. It is deemed necessary to carry out Regional Autonomy by giving broad, real, and accountable authority to the Regions in a proportional manner, which is manifested by the regulation, distribution, and utilization of natural resources. National resources, as well as central and regional financial balances, in accordance with the principles of democracy, community participation, equity, and justice, as well as the potential and diversity of the regions, which are carried out within the framework of the Unitary State of the Republic of Indonesia. So we have now arrived at the constitutional vision of life as stated in Pancasila and the 1945 Constitution, the value and meaning of political solidarity, solidarity economic, socio-cultural solidarity, and defense and security solidarity. Conclusion. The system of government Republic of Indonesia according to the 1945 Constitution gives flexibility to the Regions to carry out Regional Autonomy. In the implementation of Regional Autonomy, on the principles of democracy, community participation, equity, and justice, as well as pay attention to regional potential and diversity.